Book Hotel Maria : Hotel Mariakapel 2006-2003. - Bakker, Pedro; Lodewijks, Bart; Serafijn, Q.S.; Tuerlings, Maria; De Jongh, Xandra (Hoorn : Hotel Mariakapel Hoorn, 2006)
A book documenting the projects realised by Hotel Mariakapel (HMK) up to 2007 (co-) curated by Danielle van Zuijlen, in collaboration with artist Bart Lodewijks and guest curators.
Engels
Nederlands
boek